Urtikaria Dalam Perspektif Medis, Bioetik, Dan Islam - Muhammad Syabilal Alfat Al Buyani; Sri Vitayani; Nasrudin Andi Mappaware; Syamsu Rijal; Shulhana Mokhtar; Rachmat Faisal Syamsu (NERSMID : Jurnal Keperawatan dan Kebidanan, 2024)
Urticaria is a cutaneous reaction characterized by well-defined borders, occurring in the superficial epidermis, manifesting as wheals, erythematous and elevated lesions measuring 1-2 mm to several hours, accompanied by intense itching. In the Bioethics perspective, four fundamental principles are identified: Beneficence, non-maleficence, autonomy, and justice. From an Islamic perspective, Maqasid al-Sharia contains five values: Hifz ad din, hifz an nafs, hifz al maal, hifz al nasl, and hifz al aql. From the fiqh perspective, there are five maxims: Al umuru bi maqashida, al-dhararu yuzalu, Al masyaqqah tajlibut, Al yaqinu la yuzalu bi syaq, and Al adatu muhakkamah. Fundamental beliefs or convictions serve as a cornerstone for an individual's attitudes. These principles can be applied according to the prevailing circumstances, particularly in the field of healthcare. Based on a case report: A 40-year-old man presented to the Dermatology and Venereology Outpatient Clinic with generalized pruritic rash and bilateral swelling of the lips and eyelids since 1 day ago, occurring simultaneously. The patient was diagnosed with urticarial rash on the trunk region with angioedema of the lips and eyelids due to COVID-19 pneumonia infection. The patient's management included oral Desloratadine 5 mg, Favipiravir 600 mg, and Hydroxychloroquine 200 mg. The conclusion drawn from this case is that the patient received treatment in accordance with medical indications. Ethical considerations based on the case include autonomy and justice. From an Islamic perspective, Maqasid al-Sharia fulfills the value of Hifz al-Nafs, and from a fiqh standpoint, it adheres to the maxim of al-masyaqqah tajlibu al-taysir.